Tracer Study of BSBA Major in Human Resource Management Graduates (2017-2020) Of UM Tagum College - Raiza Mae Calbonero Narciso (LPPM of NAROTAMA UNIVERSITY, 2021)
Purpose: This study is to present the demographic profile, pursuit in higher education, employment status, industry of employment, place of employment, length of time in search of first job, methods of job search, position held at current job, training relevance to current job, skills and competencies required at work, and program contribution of UM Tagum College BSBA Human Resource Management graduates Design/methodology/approach: This study employed a research design, research respondents, research instruments, and statistical tool. Findings: while the independent variable in this study is organizational, leadership, communication, technical, decision-making, People, initiative/risk, Creativity, Team Orientation, Ability to Work Independently, Ability to Work under Pressure, and Time Management Skills are competencies that aid graduates in performing their functions. Research limitations/implications: the majority of the respondents do not belong to any professional group and do not participate in any voluntary activities. Originality/value: This study calculates and finds out the researcher requested a list of BSBA Human Resource Management graduates from the registrar's office at UM Tagum College in a letter. Paper type: Research Paper